Which is the most effective rescue treatment after the failure of mechanical thrombectomy for acute basilar artery occlusion? - Luo, Jun; Wu, Deping; Li, Zhimin; Xie, Dongjing; Huang, Jiacheng; Song, Jiaxing; Luo, Weidong; Liu, Shuai; Li, Fengli; Zi, Wenjie; Huang, Qiaojuan; Luo, Jiefeng; et al. (Frontiers in Neurology, 2022)
Objective The aim of this study was to evaluate the effectiveness and safety of rescue therapy, a therapy in which rescue devices such as balloon angioplasty, Apollo stent, Wingspan stent, Solitaire stent, or other self-expanding stents are used after the failure of mechanical thrombectomy (MT) and to determine the most effective rescue measure for acute basilar artery occlusion (BAO) after the failure of MT. Methods For this study, we recruited patients from the BASILAR registry. All participants were divided into three groups: the recanalized with rescue therapy group, the recanalized without rescue therapy group, and the non-recanalized group. Clinical outcomes at 90 days and 1 year were compared. The association of rescue measures with favorable outcomes (modified Rankin Scale [mRS] score of 0–3) in patients achieving successful recanalization via rescue therapy was estimated using multivariate logistic regression analyses. Results Among the participants, recanalization failure was found in 112 patients and successful recanalization in 473 patients, with 218 patients receiving rescue therapy and 255 patients without rescue therapy. Of these, 111 (43.5%) patients in the recanalized without rescue therapy group, 65 (29.8%) patients in the recanalized with rescue therapy group, and nine (8.0%) patients in the non-recanalized group achieved favorable outcomes at 90 days. Both the recanalization with rescue therapy and the recanalization without rescue therapy groups were associated with favorable outcomes at 90 days and 1 year compared with the non-recanalized group. Moreover, in patients receiving rescue therapy, Wingspan stents, Apollo stents, and balloon angioplasty were associated with higher rates of favorable outcomes at 90 days and 1 year than Solitaire stents. Conclusion Whether rescue therapy is administered or not, recanalization leads to favorable outcomes in patients with acute BAO. For acute BAO after MT failure, balloon angioplasty, Wingspan stenting, and Apollo stenting could be considered effective and safe rescue options but not Solitaire stenting.